Expedition to the knowledge of a science reporting on quality of life - Bertha González Fortes (Editorial Ciencias Médicas, 2014)
Being born, living, aging and dying with health is not a dream, but the future vision of man. It is impossible to separate health from the essence of man in the context of material, spiritual and moral aspects, without facing the main enemies of it: poverty, environmental deterioration, inadequate lifestyles and violence. Primary health care should be part of the general development of society, is the key to achieving an acceptable level of health for all, which helps people achieve their own economic and social development. Modern Dentistry has a fundamental objective: the conservation of dental tissues and oral diseases are increasingly more preventable in light of the development of current science. Increase and improve integral dental care through actions of promotion, prevention, healing and rehabilitation on individuals, family, community and the environment, supported by community participation and intersectoriality, in order to achieve a better state of health. oral health, raise the quality of care and the satisfaction of the population, has been the objective of the II National Symposium: VISION HEALTH BUCKAL that was held in Havana in December 2013. An exchange of experiences and debate was carried out by professionals from different provinces of Cuba on important topics: intersectoriality and population health, communication in health, quality of care, economic evaluation of preventive activities, promotion and prevention activities and its effects, different procedures and treatments of primary care. In addition, the influence of postmodernism on training and professional performance for oral health was assessed as a high risk, a subject much discussed by colleagues present. The treatment alternatives appear with a new Ayurvedic Medicine that monopolized the professional interest. We also included exhibitions of educational software that have contributed to the development of the educational process in different topics such as: Diagnosis of pain syndrome, dysfunction of the mandible, dental anomalies and dental trauma. Once again science becomes clear, everything that is done for others, for humanity, for oral health, makes us every day better health professionals and to continue our vision: ORAL HEALTH.